2014
DOI: 10.1590/1678-4499.206
|View full text |Cite
|
Sign up to set email alerts
|

Trocas gasosas e produtividade de três cultivares de meloeiro conduzidas com um e dois frutos por planta

Abstract: ResumoObjetivou-se, no presente trabalho, avaliar as trocas gasosas e sua influência na produtividade e qualidade de cultivares de melão conduzidas com um e dois frutos por planta. O experimento foi conduzido de setembro a dezembro de 2013. Utilizouse o delineamento de blocos ao acaso, em esquema fatorial 3 x 2, com seis repetições. No primeiro fator foram alocadas as cultivares de melão pertencentes aos tipos amarelo, rendilhado e pele de sapo e no segundo fator, a condução das plantas com um e dois frutos po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 8 publications
(7 reference statements)
0
16
1
9
Order By: Relevance
“…Lower Ci in plants tends to stimulate the stomatal opening, allowing greater input of CO 2 to the stomatal spaces and, which, consequently, promotes higher photosynthetic yield, as the authors observed for the treatment with 200 mL p.c./100 L H 2 O. Dalastra et al (2014), evaluating gas exchange indexes of melon cultivars conducted with one and two fruits, verified results similar to the ones found in this work for cultivar Sancho, 'Piel del Sapo', occurring simultaneously increase of A and reduction of Ci, when the plants were evaluated 56 days after transplanting.…”
Section: Resultsmentioning
confidence: 71%
“…Lower Ci in plants tends to stimulate the stomatal opening, allowing greater input of CO 2 to the stomatal spaces and, which, consequently, promotes higher photosynthetic yield, as the authors observed for the treatment with 200 mL p.c./100 L H 2 O. Dalastra et al (2014), evaluating gas exchange indexes of melon cultivars conducted with one and two fruits, verified results similar to the ones found in this work for cultivar Sancho, 'Piel del Sapo', occurring simultaneously increase of A and reduction of Ci, when the plants were evaluated 56 days after transplanting.…”
Section: Resultsmentioning
confidence: 71%
“…These authors denote that all the photosynthetic pigments decreased with the increase of electrical conductivity, with chlorophyll being more sensitive to salinity. Dalastra et al (2014) evaluated the gas exchange in three melon cultivars, conducted with one and two fruits, and found that the cultivars differed significantly, being Sancho superior to Medellin and Grand Prix, with 9.23 % and 11.30 %, respectively. That is, there is diversity in the physiology of plants of the same species.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Natal and Goldex cultivars exceed the intercellular CO 2 concentration, with an increase up to 0.66 dS m -1 and 2.01 dS m -1 , respectively, declining sharply from these levels. Higher CO 2 concentrations support high photosynthetic rates, while, at very low intercellular CO 2 concentrations, photosynthesis is limited (Dalastra et al 2014). This photosynthetic variable is crucial for yield.…”
Section: Resultsmentioning
confidence: 99%
“…As a means of alleviating the stress effect, the plant can close its stomata, reducing water absorption and consequently the entrance of toxic salts. Closure of the stomata may result in a decreased transpiration, and internal CO 2 concentration in leaves (Dalastra et al, 2014). Therefore, plant diminishes its photosynthetic processes, the fixation of CO 2 and the production of photoassimilates.…”
Section: Resultsmentioning
confidence: 99%